On rock as an alternative materiality to access “structures of feeling”: the Velvet Underground’s case and the pop music scenario in late’ 1960’s (Per Musi, 2018)
Starting from the hypothesis that rock music can be considered as a kind of alternative materiality to access the culture of a period, Velvet Underground’s album White Light/White Heat (1968) is addressed in this paper considering one of the contexts observed in late 1960’s. The academic education of the band members, as well as the Pop Art as proposed by Andy Warhol, and the way of life observed at the Factory studio are analyzed as parts that contribute to the constitution of a “structure of feeling”. The hypothesis is reinforced with a brief comparison between White Light/White Heat and the White Album from the Beatles, what presents the possibility of access to distinct cultures of the same period by rock music analysis.